### 11 Answers

You just plug in these numbers for variables. For instance:

36(3)-8(-6)^2=

108-288=

-180

Hopefully, that helps you.

Hooah!

Find 36x – 8y^2 when x = 3 and y = -6

Replacing variables with values:

36*(3) – 8*(-6)^2

=108 – 8*(36) ( (-6)^2 = 6^2, whenever a negative number is raised to an even power, it becomes positive)

= 108 – 288

= -180

Thus, the result is (-180)

36x – 8y^2

when x= 3 & y = – 6

so 36x – 8y^2 = 36*3- 8*36= 36[ 3- 8]

=- 36*5 = – 180

36x – 8yÂ² when x = 3 and y = -6

= 36(3) – 8(-6)^2

= – 180 answer..

36x-8y^2 = 36(3) – 8(-6)^2 = 108-8(-6)^2 = 108-288 = -180.

Just put the values and calculate… it is 36*3 -8*(-6)^2 = 108 – 288 = – 180 OK!

36*3 – 8*(-6)^2

= 108 – 8*36

= 108 – 288

= -180 <<<

value is 36(3) – 8(-6)^2

= 36(3) – 8(36)

= 36(3 – 8)

= 36(-5)

= -180

-180

-180